WOMEN AT THE CENTRE: A READING OF EASTERINE KIRE’S A TERRIBLE MATRIARCHY - C. R.V. Sindhu; Bose, A. Xavier Chandra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Women of different ages, of different roles as daughters, mothers and wives; of different geographical, social and familial backgrounds; and of different emotional, psychological dispositions inhabit the fictional world of Easterine Kire, a well-known North-East Indian Naga writer. It can be well noticed that all the actions of her fictional world revolve around her land, women and men of Nagaland. The present paper focusses on the three generations of Naga women: Grandmother, mother and Dielieno, the protagonist of the novel.